Health monitoring smart device for firefighters - Pervez, Asif Muhammed; Ahmed, Abid Mustakem; Diba, Iffat Ara; Azad, Shahriar (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.